Research on Calculation Method of Meshing Stiffness of Straight Bevel Gear - Siyu Chen; Rulong Tan; Xiaodong Guo (Jixie chuandong)
Aiming at the calculation problem of straight bevel gear meshing stiffness， to convert the tooth to tooth width of midpoint equivalent straight tooth cylindrical gear， then the equivalent of the gear tooth is simplified to the cantilever beam on the dedendum circle， through the energy method， the single tooth meshing stiffness is calculated the analyzed. Based on the principle of displacement tolerance further gear time-varying meshing stiffness calculation model is put forward. Compared with the finite element results， and the source of the error is analyzed， the verification of the calculation method is completed. The proposed calculation method not only enriches and develops the calculation theory of gear stiffness， but also has important significance to the study of gear dynamics.